1999
DOI: 10.2214/ajr.173.1.10397125
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas divisum: implications for diagnostic and therapeutic pancreatography.

Abstract: OBJECTIVE.The purpose ofour study was to determine the prevalence, distribution, and clinical Clinical indications for and therapy during ERCP were correlated with radiographic findings. RESULTS.Of the 94 patients with pancreas divisum, 54 (57%) had radiographic evidence of pancreatitis.Of these 54 patients, 44 had at least one episode of clinically documented pancreati- CONCLUSION.In our population ofpatients referred for ERCP and found to have pancreas divisum, the prevalence ofpancreatitis was very high an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 16 publications
0
37
0
1
Order By: Relevance
“…On the other hand, ERCP studies demonstrated an increased frequency of pancreas divisum in patients with signs of a pancreatitis [16,31,32]. However, these ERCP studies are of limited value as they included only symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ERCP studies demonstrated an increased frequency of pancreas divisum in patients with signs of a pancreatitis [16,31,32]. However, these ERCP studies are of limited value as they included only symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 The prevalence of PD in RAP varies across various studies (Table 6). 25,[35][36][37][41][42][43] A recent community-based study from Japan included 504 subjects from the general population, and 46 patients with pancreatitis (8 AP, 23 CP and 15 RAP). PD was present in 35% of patients with pancreatitis versus 2.6% in the general community and had an odds ratio of 23.4 for inducing pancreatitis.…”
Section: Pancreas Divisum (Pd)mentioning
confidence: 99%
“…Other than pancreas divisum (incomplete fusion) and annular pancreas (forming a ring around the duodenum) (Fig. 8.21 ), anatomic variants have no clinical relevance (Morgan et al 1999 ).…”
Section: The Pancreasmentioning
confidence: 99%